SIFAT PENGERINGAN ALAMI DAN DEHUMIDIFIKASI BEBERAPA JENIS KAYU INDONESIA - Syarif Hidayat; Suparman Karnasudirdja (Jurnal Penelitian Hasil Hutan, 1987)
This paper presents results of laboratory study  on the rate of moisture  content  decrease of 19 timber species.  The test specimen from each species were subjected  to air drying under sheltered condition  (under roof) and drying in a dehumidifying chamber.  At the end of each test.  the defect of each specimen  was recorded, and the most appropriate form of relation between duration  of drying and moisture  content  decrease was sought.From data analysis it was shown that a power form of relationship (Y = aXb) was reasonable, with coefficient  of correlation values varying between  0.80-0.90.The result also shows  that the longest air drying time (from 60% to 20%  moisture  content)  was recorded by kayu besi (53 days) and the shortest  by dama-dama  and palapi  (18 days).As  has been anticipated,  drying  in the dehumidifier   has reduced  considerably  the time  required for  drying from 60% to 20% moisture content. For example for the three species mentioned  above  the figures  were 20 days for  kayu  besi and 5 days for  dama-dama  and palapi.The result shows further  that severe defect was observed in kolaka,  bugis, suling and belu itam.  The remaining species have either moderate or slight defect.